A comparison of investor attractiveness of oil and gas exploration and production regulatory environments and fiscal regimes in South Africa and Mozambique - Sigedle, Anelisa (My University, 2022)
The petroleum industry plays an important role both in South Africa (SA) and Mozambique’s economies. It is one of the most important sources of energy and the largest single commodity in international trade. This study aimed to explore and compare the fiscal policies of Mozambique and SA in respect of the attractiveness of the fiscal regime used to attract investment to South Africa as opposed to Mozambique. The study explored the evolution of policies in both countries. This was done by comparing the fiscal regimes using a hypothetical case model for both countries, which applied different tax rates and state participation in an oil field project. Net present value (NPV) and internal rate of return (IRR) were used to evaluate the project success and how much the government or the contractor stands to make from the different fiscal regimes. The results showed that the project NPV is highest for the investor when the proposed Mineral Petroleum Resource Bill is applied than the current Mineral and Petroleum Resources Development Act (MPRDA) and the Petroleum Law in Mozambique. The results also showed that the proposed fiscal regime in SA will decrease the NPV for the investor, which makes it less attractive. The study showed that increased state participation has a greater impact on changing the contractor’s NPV. If these two governments want to encourage investors to continue exploration in their countries, there should be a balance between the profit that companies make and the revenue that the governments can collect. Thus, the policy recommendation for SA includes having negotiable royalties that promote investment in exploration and increase resources in oil and gas.
A research report submitted to the Wits Business School in the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Energy Leadership
Keywords: Exploration and production; Fiscal regime; Investor attractiveness; Mozambique; Oil and gas regulatory dispensations; South Africa; SDG-8: Decent work and economic growth